Extending the scope of protection to domestic violence victims in relation to employment entitlements - Randawar, Daleleer Kaur; Ibrahim, Norliah; Che Soh @ Yusoff, Roslina (LexisNexis Malaysia Sdn. Bhd., 2018)
The issue of domestic violence is not new in Malaysia. This abuse that happens in a family or sometimes personal relationship often has a ripple effect that haunts through the fabric of the victim's life. In some cas-es, domestic violence spills into the workplace, with devastating consequences for victims, their colleagues, and their employers. Sometimes victims find it difficult to deal with their employers who fail to understand their hardship. Instead of employers relieving their plight, they make it more distressful for the victims. Vic-tims of domestic violence may also at times be targets of employment discrimination. Hence, victims who suffer violence require proper support services to assist them to lessen the hardship they have to endure at the workplace. Certain employment policies that can protect the rights of victims of violence need to be im-plemented to prevent them from losing their jobs and facing discrimination at their workplace. Providing proper support under the law by expanding employment rights for the victim of domestic violence such as paid leave or reasonable time off from work will lessen the agony of an employed victim. This article focuses on analysing the differences, special and unique features of the employment entitlement and benefits under the domestic violence law in some selected jurisdictions.